2000
DOI: 10.1108/03074350010766882
|View full text |Cite
|
Sign up to set email alerts
|

Changes in corporate management: do they have an impact on share prices and company earnings?

Abstract: 2011),"Earnings per share versus cash flow per share as predictor of dividends per share", Managerial Finance, Vol. 37 Iss 5 pp. 482-488 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
4
0
6
Order By: Relevance
“…This is because, in a short period of time, investors might not be able to evaluate the contribution and performance of the new CEO/MD. This is consistent with the studies of Ishak et al (2013) and Dahyaa et al (2000) which concluded that improvement in post-succession performance can only be realized at least two years after the CEO/MD assumes the position.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This is because, in a short period of time, investors might not be able to evaluate the contribution and performance of the new CEO/MD. This is consistent with the studies of Ishak et al (2013) and Dahyaa et al (2000) which concluded that improvement in post-succession performance can only be realized at least two years after the CEO/MD assumes the position.…”
Section: Resultssupporting
confidence: 81%
“…Fanelli & Grasselli 2006;Tosi, Misangyi, Fanelli, Waldman & Yammarino 2004;Waldman, Ramirez, House & Puranam 2001), which provided evidence that CEO's charisma affects the perceptions of external stakeholders and share prices. However, as reported by Dahyaa et al (2000), relatively small or insignificant share price response was observed in earlier studies (such as Ishak & Abdul Latif 2012;Setiawan et al 2011;Cools & van Praag 2007;Warner, Watts & Wruck 1988), whereby this situation is due to investors' uncertainty of whether the performance of the "new" management is better than its predecessor (Dahyaa et al 2000).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations